GAMBARAN SOSIO DEMOGRAFI, PENGETAHUAN, DAN SIKAP IBU DALAM MELAKUKAN PENIMBANGAN BALITA DI POSYANDU DESA JAMBUR PULAU KECAMATAN PERBAUNGAN TAHUN 2016 - Desy Tiara Dipa; Jumirah .; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Under-five-years-old children weighing in Posyandu useful for monitoring the health and growth of under-five-years-old children. This study aimed to describe the socio demographic, knowledge, and attitudes of mothers in under-five-years-old children weighing in Posyandu Jambur Pulau Perbaungan Subdistrict in 2016. The type of this research is decriptive research with cross sectional design. The population are mothers who have children aged 12-36 months. The sampling technique is sistematic random sampling, sample size is 63 people. The research instrument are questionnaire on maternal characteristics, growth chart (KMS), and weighing notes of posyandu. The data was collected then analyzed descriptively. The results showed that most of mothers didn’t regularly weigh their children to Posyandu was equal to 60.3%, results of cross tabulation showed that women with > 2 under-five-years-old children didn’t regularly weigh their children to posyandu (79.4%), mothers with low education (100%) didn’t regularly weigh their children to Posyandu, working mothers didn’t regularly weigh their children to posyandu (85.7 %), mothers who live near from posyandu didn’t regularly weigh their children to posyandu (94.4%). Mothers with less knowledge didn’t regularly weigh their children to Posyandu (90.6%) and mother has bad attitude on posyandu didn’t regularly weigh their children to posyandu (96.4%). People of Jambur Pulau especially mothers should get education/counseling about function of posyandu and the importance of under-five-years-old children's weight to increase awareness of mothers in monitoring the growth status of children and expected have an impact on the regularity of a under-five-years-old children's weight at least eight times a year. Keywords : socio-demographic, knowledge, attitudes, under-five-years-old children weighing